1978
DOI: 10.1128/aem.36.2.243-246.1978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fungi during Skylab missions

Abstract: Samples for mycological analysis were collected from surfaces in the Skylab spacecraft before launch and during flight for each manned mission. Fungal contamination levels were low during the first two flights; however, the species recovered were different for each mission. On the third mission, widespread contamination of the Skylab spacecraft with Aspergillus and Pencillium spp. was detected. This contamination was traced to several contaminated space suit undergarments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…These results suggest that the fungal biota of orbital samples would be similar to those of the door push plate on the ground. Cultures have indicated that the dominant fungal species belong to the genera Aspergillus , Penicillium , and Cladosporium on both space station Mir and Skylab (1, 2). The results of the present study indicate that, after Malassezia , Cladosporium was the next most dominant genus in orbit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the fungal biota of orbital samples would be similar to those of the door push plate on the ground. Cultures have indicated that the dominant fungal species belong to the genera Aspergillus , Penicillium , and Cladosporium on both space station Mir and Skylab (1, 2). The results of the present study indicate that, after Malassezia , Cladosporium was the next most dominant genus in orbit.…”
Section: Discussionmentioning
confidence: 99%
“…were detected (1). The dominant species of fungi detected on Mir and the USA space station Skylab belonged to the genera Aspergillus, Penicillium, and Cladosporium (1,2). On the ground, there have been some reports of cases with symptoms similar to the allergic disease sick building syndrome, which occurs in people living in places with heavy Aspergillus and Penicillium infestation (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental monitoring data have shown that the wide variety of microorganisms isolated from spacecraft are largely of human origin (1)(2)(3)(4)(5). Doctors and researchers are fully aware of the risk that fungal infection that could cause serious life-threatening disease in long-term space expeditions.…”
mentioning
confidence: 99%
“…Accordingly, a number of microorganisms progressively contaminate the living and working environments of spacecraft from the beginning of construction (1). Researchers have found large numbers of microorganisms in the cabins of space stations, such as the Russian Mir Space Station and the ISS, some of which are pathogenic microorganisms, including opportunistic fungi (1–5). Because they are in a limited and confined space, astronauts and on board equipment would be continuously exposed to high concentrations of fungal spores.…”
mentioning
confidence: 99%